Antistatic lithium ion battery soft coating film and preparation process thereof
By using carbon black and graphene as antistatic layers on the soft coat of lithium-ion batteries and enhancing its antistatic properties through hot pressing technology, the problem that the soft coat of lithium-ion batteries cannot effectively antistatic when used is solved, which is significantly Improves the safety of lithium-ion batteries.
Patent Information
- Application Number
- CN202411060698.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-05
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing soft lithium-ion battery capsules cannot effectively anti-static electricity when used, resulting in low safety of lithium-ion batteries and risk of fire and explosion.
Carbon black and graphene are used as antistatic layers, and they are applied to the composite base layer through hot pressing technology to form an antistatic layer with a thickness ratio of 1:0.1-0.4, enhancing the antistatic properties of the soft coat of lithium-ion batteries.
Effectively prevent static electricity, improve the safety of lithium-ion batteries, and significantly improve the anti-static performance of lithium-ion batteries.
Smart Images

Figure CN119170964A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion battery soft package films, in particular to an antistatic lithium ion battery soft package film and a preparation process thereof. Background Art
[0002] Lithium-ion battery is a secondary battery (rechargeable battery) that mainly relies on the movement of lithium ions between the positive electrode and the negative electrode to work. During the charge and discharge process, Li+ is embedded and de-embedded between the two electrodes: when charging, Li+ is de-embedded from the positive electrode and embedded in the negative electrode through the electrolyte, and the negative electrode is in a lithium-rich state; when discharging, the opposite is true. As an important energy supply for modern electronic devices, the safety of lithium-ion batteries is increasingly valued by people.
[0003] Among them, the static electricity problem is an important factor affecting the safety of lithium-ion batteries. During the production, storage and use of lithium-ion batteries, static electricity is easily generated due to friction or electrochemical reactions between raw materials, components, electrolytes and other substances. If it cannot be discharged in a timely and effective manner, it will cause damage to the battery and may even cause serious consequences such as fire and explosion.
[0004] The existing lithium-ion battery soft-package film cannot effectively resist static electricity when in use, resulting in low safety in the use of lithium-ion batteries. Summary of the invention
[0005] The purpose of the present invention is to provide an antistatic lithium-ion battery soft-package film and a preparation process thereof, wherein carbon black and graphene are used as the antistatic layer, and the antistatic layer is hot pressed on a composite base layer. The antistatic layer can prevent static electricity, so that the lithium-ion battery soft-package film can effectively resist static electricity when in use, thereby improving the safety of lithium-ion batteries and solving the problems raised in the above-mentioned background technology.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] An antistatic lithium-ion battery soft package film comprises a composite base layer and an antistatic layer, wherein the antistatic layer is hot pressed on the composite base layer, and the thickness ratio of the composite base layer to the antistatic layer is 1:0.1-0.4.
[0008] Preferably, the composite base layer comprises a nylon layer, an aluminum layer and a polypropylene layer, one end surface of the aluminum layer is provided with the nylon layer, and the other end surface of the aluminum layer is provided with the polypropylene layer.
[0009] Preferably, the nylon layer and the polypropylene layer are respectively bonded to the two sides of the aluminum layer by an adhesive, wherein the adhesive is one of an epoxy resin adhesive and a polyurethane adhesive.
[0010] Preferably, the nylon layer is made of nylon material, which is stirred, mixed, plasticized, pressed, extruded and stretched by an extrusion molding machine to form a calendered film with uniform thickness, and the calendered film is sheared to form a nylon layer that meets size requirements.
[0011] Preferably, the aluminum layer is made of aluminum material as raw material, and is stirred, mixed, plasticized, pressed, extruded and stretched by an extrusion molding machine to form a calendered film with uniform thickness, and the calendered film is sheared to form an aluminum layer that meets size requirements.
[0012] Preferably, the polypropylene layer is made of polypropylene material, and is stirred, mixed, plasticized, pressed, extruded and stretched by an extrusion molding machine to form a calendered film with uniform thickness, and the calendered film is sheared to form a polypropylene layer that meets size requirements.
[0013] Preferably, the thickness ratio of the nylon layer, the aluminum layer and the polypropylene layer is 1:0.8-1.6:1.
[0014] Preferably, the antistatic layer comprises the following raw materials in parts by mass: 0-10 parts of carbon black and 0-8 parts of graphene.
[0015] Preferably, the specific surface area of the carbon black is 280-350m 2 / g, particle size is 10-15um.
[0016] According to another aspect of the present invention, there is provided a process for preparing the above-mentioned antistatic lithium-ion battery soft film, comprising the following steps:
[0017] S1. Preparation of composite base layer:
[0018] The nylon material, the aluminum material and the polypropylene material are respectively added into the extrusion molding machine, and the extrusion molding machine is used to stir, mix, plasticize, press, extrude and extend to form a calendered film with uniform thickness, and the calendered film is sheared to form a nylon layer, an aluminum layer and a polypropylene layer that meet the size requirements;
[0019] Applying adhesive to the nylon layer, the aluminum layer and the polypropylene layer, so that the nylon layer and the polypropylene layer are respectively bonded to the two sides of the aluminum layer through the adhesive;
[0020] The bonded nylon layer, aluminum layer and polypropylene layer are subjected to heat pressing to form a composite base layer;
[0021] S2. Preparation of lithium-ion battery soft film:
[0022] The antistatic layer is evenly arranged on the composite base layer, and the composite base layer and the antistatic layer are subjected to hot pressing treatment, wherein the pressure is 20-30MPa, the temperature is 180-200°C, and the time is 5-16min. After cooling and shaping, a lithium ion battery soft film is formed.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] The present invention adopts carbon black and graphene as the antistatic layer, and hot presses the antistatic layer on the composite base layer. The antistatic layer can prevent static electricity, so that the lithium ion battery soft package film can effectively resist static electricity when in use, and the safety of lithium ion batteries can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a schematic structural diagram of the antistatic lithium-ion battery soft package film of the present invention;
[0026] Figure 2 It is a schematic diagram of the development of the composite base layer of the present invention.
[0027] In the figure: 1, composite base layer; 11, nylon layer; 12, aluminum layer; 13, polypropylene layer; 2, antistatic layer. DETAILED DESCRIPTION
[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] In order to solve the problem that the existing lithium-ion battery soft film cannot effectively resist static electricity during use, resulting in low safety of lithium-ion batteries, please refer to Figure 1-Figure 2 , this embodiment provides the following technical solutions:
[0030] Embodiment 1
[0031] An antistatic lithium-ion battery soft film comprises a composite base layer 1 and an antistatic layer 2, wherein the antistatic layer 2 is hot pressed on the composite base layer 1, and the thickness ratio of the composite base layer 1 to the antistatic layer 2 is 1:0.1-0.4.
[0032] In this embodiment, as a preferred technical solution of the present invention, the composite base layer 1 includes a nylon layer 11, an aluminum layer 12 and a polypropylene layer 13, wherein the nylon layer 11 is disposed on one end surface of the aluminum layer 12, and the polypropylene layer 13 is disposed on the other end surface of the aluminum layer 12.
[0033] In this embodiment, as a preferred technical solution of the present invention, the nylon layer 11 and the polypropylene layer 13 are respectively bonded to the two sides of the aluminum layer 12 by an adhesive, wherein the adhesive is one of an epoxy resin adhesive and a polyurethane adhesive.
[0034] It should be noted that the nylon layer 11 and the polypropylene layer 13 are respectively bonded to the two sides of the aluminum layer 12 by an adhesive, so that the nylon layer 11, the aluminum layer 12 and the polypropylene layer 13 are evenly and firmly connected together, which can fully protect the lithium-ion battery.
[0035] In this embodiment, as the preferred technical solution of the present invention, the nylon layer 11 is made of nylon material as raw material, and is stirred, mixed, plasticized, pressed, extruded and stretched by an extrusion molding machine to form a calendered film with uniform thickness, and the calendered film is sheared to form a nylon layer 11 that meets the size requirements.
[0036] In this embodiment, as the preferred technical solution of the present invention, the aluminum layer 12 uses aluminum material as raw material, and is stirred, mixed, plasticized, pressed, extruded and stretched by an extrusion molding machine to form a calendered film with uniform thickness, and the calendered film is sheared to form an aluminum layer 12 that meets the size requirements.
[0037] In this embodiment, as the preferred technical solution of the present invention, the polypropylene layer 13 is made of polypropylene material as raw material, and is stirred, mixed, plasticized, pressed, extruded and stretched by an extrusion molding machine to form a calendered film with uniform thickness, and the calendered film is sheared to form a polypropylene layer 13 that meets the size requirements.
[0038] In this embodiment, as a preferred technical solution of the present invention, the thickness ratio of the nylon layer 11, the aluminum layer 12 and the polypropylene layer 13 is 1:0.8-1.6:1.
[0039] It should be noted that the nylon layer 11 can ensure the appearance of the lithium-ion battery soft package film and ensure that the lithium-ion battery soft package film will not be deformed.
[0040] It should be noted that the function of the aluminum layer 12 is to prevent water from penetrating. Lithium-ion batteries are very afraid of water, and generally require the water content of the electrode to be at the PPM level. Therefore, the soft package film of the lithium-ion battery must be able to block the penetration of water vapor. The nylon layer 11 is not waterproof and cannot play a protective role. Metal aluminum will react with oxygen in the air at room temperature to form a dense oxide film, which prevents water vapor from penetrating and protects the interior of the battery cell.
[0041] It should be noted that the polypropylene layer 13 will melt at a temperature of more than 100 degrees Celsius and has viscosity. Therefore, the thermal packaging of the lithium-ion battery mainly relies on the polypropylene layer 13.
[0042] In this embodiment, as a preferred technical solution of the present invention, the antistatic layer 2 includes the following raw materials in parts by mass: 10 parts of carbon black and 8 parts of graphene.
[0043] In this embodiment, as the preferred technical solution of the present invention, the specific surface area of carbon black is 280-350m 2 / g, particle size is 10-15um.
[0044] It should be noted that by hot pressing the antistatic layer 2 on the composite base layer 1, static electricity can be prevented through the antistatic layer 2, so that the lithium-ion battery soft package can effectively resist static electricity when in use, thereby improving the safety of lithium-ion batteries.
[0045] In order to better demonstrate the preparation process of the antistatic lithium-ion battery soft film, this embodiment now provides a preparation process of the antistatic lithium-ion battery soft film, including the following steps:
[0046] S1. Preparation of composite base layer 1:
[0047] The nylon material, the aluminum material and the polypropylene material are respectively added into the extrusion molding machine, and the extrusion molding machine is used to stir, mix, plasticize, press, extrude and extend to form a calendered film with uniform thickness, and the calendered film is sheared to form a nylon layer 11, an aluminum layer 12 and a polypropylene layer 13 that meet the size requirements;
[0048] Applying adhesive to the nylon layer 11, the aluminum layer 12 and the polypropylene layer 13, so that the nylon layer 11 and the polypropylene layer 13 are respectively bonded to the two sides of the aluminum layer 12 by the adhesive;
[0049] The bonded nylon layer 11, aluminum layer 12 and polypropylene layer 13 are subjected to heat pressing treatment to form a composite base layer 1;
[0050] S2. Preparation of lithium-ion battery soft film:
[0051] The antistatic layer 2 is evenly arranged on the composite base layer 1, and the composite base layer 1 and the antistatic layer 2 are subjected to hot pressing treatment, wherein the pressure is 20-30MPa, the temperature is 180-200°C, and the time is 5-16min. After cooling and shaping, a lithium ion battery soft film is formed.
[0052] Embodiment 2
[0053] The only difference from the first embodiment is that the antistatic layer 2 is different;
[0054] The antistatic layer 2 includes the following raw materials in parts by mass: 10 parts of carbon black.
[0055] Among them, the specific surface area of carbon black is 280-350m 2 / g, particle size is 10-15um.
[0056] Compared with Example 1, graphene is eliminated in Example 2, and the lithium-ion battery soft envelope film is prepared by the same preparation process as Example 1.
[0057] Embodiment 3
[0058] The only difference from the first embodiment is that the antistatic layer 2 is different;
[0059] The antistatic layer 2 includes the following raw materials in parts by mass: 8 parts of graphene.
[0060] Compared with Example 1, carbon black is eliminated in Example 3, and the lithium ion battery soft film is prepared by the same preparation process as Example 1.
[0061] Comparative Example
[0062] An antistatic lithium-ion battery soft package film comprises a composite base layer 1.
[0063] The composite base layer 1 comprises a nylon layer 11 , an aluminum layer 12 and a polypropylene layer 13 . The nylon layer 11 is disposed on one end surface of the aluminum layer 12 , and the polypropylene layer 13 is disposed on the other end surface of the aluminum layer 12 .
[0064] In this embodiment, as a preferred technical solution of the present invention, the nylon layer 11 and the polypropylene layer 13 are respectively bonded to the two sides of the aluminum layer 12 by an adhesive, wherein the adhesive is one of an epoxy resin adhesive and a polyurethane adhesive.
[0065] In this embodiment, as the preferred technical solution of the present invention, the nylon layer 11 is made of nylon material as raw material, and is stirred, mixed, plasticized, pressed, extruded and stretched by an extrusion molding machine to form a calendered film with uniform thickness, and the calendered film is sheared to form a nylon layer 11 that meets the size requirements.
[0066] In this embodiment, as the preferred technical solution of the present invention, the aluminum layer 12 uses aluminum material as raw material, and is stirred, mixed, plasticized, pressed, extruded and stretched by an extrusion molding machine to form a calendered film with uniform thickness, and the calendered film is sheared to form an aluminum layer 12 that meets the size requirements.
[0067] In this embodiment, as the preferred technical solution of the present invention, the polypropylene layer 13 is made of polypropylene material as raw material, and is stirred, mixed, plasticized, pressed, extruded and stretched by an extrusion molding machine to form a calendered film with uniform thickness, and the calendered film is sheared to form a polypropylene layer 13 that meets the size requirements.
[0068] In this embodiment, as a preferred technical solution of the present invention, the thickness ratio of the nylon layer 11, the aluminum layer 12 and the polypropylene layer 13 is 1:0.8-1.6:1.
[0069] Compared with Example 1, the antistatic layer 2 is eliminated in the comparative example, and the lithium ion battery soft film is prepared by the same preparation process as Example 1, while the preparation step of the antistatic layer 2 is eliminated.
[0070] The performance tests were conducted on the lithium ion battery soft film prepared in Examples 1-3 and the comparative example, wherein the performance test results of the lithium ion battery soft film are shown in Table 1:
[0071] Table 1: Performance test results of lithium-ion battery soft film
[0072] Embodiment 1 Embodiment 2 Embodiment 3 Comparative Example Antistatic layer / yes, no have have have none Carbon black / mass fraction 10 10 0 0 Graphene / mass fraction 8 0 8 0 Antistatic performance / 100% 97.34% 96.15% 95.86% 84.29%
[0073] Therefore, it can be seen from the above table that the lithium ion battery soft coating films prepared in Examples 1-3 all have good antistatic properties and can improve the safety of lithium ion batteries.
[0074] Among them, compared with Example 1, the antistatic performance of Example 2 is reduced. Since graphene is not added in Example 2, the antistatic performance of the lithium-ion battery soft film is reduced, which shows that graphene can improve the antistatic performance of the lithium-ion battery soft film.
[0075] Among them, compared with Example 1, the antistatic performance of Example 3 is reduced. Since carbon black is not added in Example 3, the antistatic performance of the lithium-ion battery soft film is reduced, which shows that carbon black can improve the antistatic performance of the lithium-ion battery soft film.
[0076] Among them, compared with Example 1, the antistatic performance of the comparative example is reduced. Since the antistatic layer 2 is not added in the comparative example, the antistatic performance of the lithium-ion battery soft film is reduced, which shows that the antistatic layer 2 can improve the antistatic performance of the lithium-ion battery soft film.
[0077] Therefore, by hot pressing the antistatic layer 2 on the composite base layer 1, static electricity can be prevented through the antistatic layer 2, so that the lithium-ion battery soft package film can effectively resist static electricity when in use, and the safety of lithium-ion batteries can be improved.
[0078] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0079] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. An antistatic lithium-ion battery soft film, comprising a composite base layer (1) and an antistatic layer (2), characterized in that: The antistatic layer (2) is hot pressed onto the composite base layer (1), and the thickness ratio of the composite base layer (1) to the antistatic layer (2) is 1:0.1-0.
4.
2. The antistatic lithium-ion battery soft film according to claim 1, characterized in that: The composite base layer (1) comprises a nylon layer (11), an aluminum layer (12) and a polypropylene layer (13); the nylon layer (11) is arranged on one end surface of the aluminum layer (12), and the polypropylene layer (13) is arranged on the other end surface of the aluminum layer (12).
3. The antistatic lithium-ion battery soft film according to claim 2, characterized in that: The nylon layer (11) and the polypropylene layer (13) are respectively bonded to the two sides of the aluminum layer (12) by means of an adhesive, wherein the adhesive is one of an epoxy resin adhesive and a polyurethane adhesive.
4. The antistatic lithium-ion battery soft film according to claim 2, characterized in that: The nylon layer (11) is made of nylon material and is stirred, mixed, plasticized, pressed, extruded and stretched by an extrusion molding machine to form a calendered film with uniform thickness. The calendered film is sheared to form a nylon layer (11) that meets size requirements.
5. The antistatic lithium-ion battery soft film according to claim 2, characterized in that: The aluminum layer (12) is made of aluminum material as raw material, and is stirred, mixed, plasticized, pressed, extruded and stretched by an extrusion molding machine to form a calendered film with uniform thickness, and the calendered film is sheared to form an aluminum layer (12) that meets size requirements.
6. The antistatic lithium-ion battery soft film according to claim 2, characterized in that: The polypropylene layer (13) is made of polypropylene material and is stirred, mixed, plasticized, pressed, extruded and stretched by an extrusion molding machine to form a calendered film with uniform thickness. The calendered film is sheared to form a polypropylene layer (13) that meets size requirements.
7. The antistatic lithium-ion battery soft film according to claim 2, characterized in that: The thickness ratio of the nylon layer (11), the aluminum layer (12) and the polypropylene layer (13) is 1:0.8-1.6:
1.
8. The antistatic lithium-ion battery soft film according to claim 1, characterized in that: The antistatic layer (2) comprises the following raw materials in parts by mass: 0-10 parts of carbon black and 0-8 parts of graphene.
9. The antistatic lithium-ion battery soft film according to claim 8, characterized in that: The specific surface area of the carbon black is 280-350m 2 / g, particle size is 10-15um.
10. A process for preparing an antistatic lithium-ion battery soft film according to any one of claims 1 to 9, characterized in that: The steps include: S1. Preparation of composite base layer (1): The nylon material, the aluminum material and the polypropylene material are respectively added into an extrusion molding machine, and stirred, mixed, plasticized, pressed, extruded and stretched by the extrusion molding machine to form a calendered film with uniform thickness, and the calendered film is sheared to form a nylon layer (11), an aluminum layer (12) and a polypropylene layer (13) that meet the size requirements; Coating an adhesive on the nylon layer (11), the aluminum layer (12) and the polypropylene layer (13), so that the nylon layer (11) and the polypropylene layer (13) are respectively bonded to both sides of the aluminum layer (12) through the adhesive; The bonded nylon layer (11), aluminum layer (12) and polypropylene layer (13) are subjected to heat pressing treatment to form a composite base layer (1); S2. Preparation of lithium-ion battery soft film: The antistatic layer (2) is evenly arranged on the composite base layer (1), and the composite base layer (1) and the antistatic layer (2) are subjected to a hot pressing treatment, wherein the pressure is 20-30 MPa, the temperature is 180-200° C., and the time is 5-16 minutes. After cooling and shaping, a lithium ion battery soft film is formed.
Citation Information
Patent Citations
Lithium ion battery packaging film, lithium ion battery packaging method, and lithium ion battery prepared therewith
CN108615828A
Aluminum-plastic compound film used for anti-pollution polymer lithium-ion power battery and preparation method thereof
CN108735921A
Composite diaphragm, battery and manufacturing method of composite diaphragm
CN112635913A
Novel insulating cell membrane
CN208580814U
A protective film for Anti-static and electromagnetic wave shielding and the manufacturing method thereof
KR1020080093928A
